2022
DOI: 10.19184/jtc.v6i2.31456
|View full text |Cite
|
Sign up to set email alerts
|

Digitalisasi Media Promosi Desa Wisata Penglipuran Bali Melalui Program Magang Bersertifikat

Abstract: The existence of digital technology today that has become a mandatory tool that is easy to use for good or bad with a wide and unlimited reach is social media. Penglipuran Tourism Village as one of the leading tourist villages in Bali is still not maximal in utilizing social media, especially the simplest Instagram. Certified Internship Program managed by Pigijo and Kemendikbudristek is expected to increase the digitization of tourist villages that are partners. Penglipuran became one of the partners assigned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
1
0
3
Order By: Relevance
“…Wisatawan memiliki kecenderungan untuk membandingkan pengalaman-pengalaman langsung selama melakukan kunjungan ke suatu destinasi wisata (Busaini et al, 2020). Memiliki target pasar juga memberikan peluang untuk melakukan kegiatan kolaboratif bersama pemerintah setempat dan tim pengelola peningkatan desa sebagai pengembangan desa yang lebih luas (Rokhani & Hafidhuddin, 2022).…”
Section: Target Pasarunclassified
“…Wisatawan memiliki kecenderungan untuk membandingkan pengalaman-pengalaman langsung selama melakukan kunjungan ke suatu destinasi wisata (Busaini et al, 2020). Memiliki target pasar juga memberikan peluang untuk melakukan kegiatan kolaboratif bersama pemerintah setempat dan tim pengelola peningkatan desa sebagai pengembangan desa yang lebih luas (Rokhani & Hafidhuddin, 2022).…”
Section: Target Pasarunclassified
“…Dengan adanya website desa, masyarakat Desa Gunung Malelo akan memiliki akses mudah dan cepat terhadap informasi-informasi penting, seperti pengumuman dari pemerintah desa, kegiatankegiatan sosial, informasi dan lain sebagainya. Selain itu, website desa juga dapat menjadi wadah untuk mempromosikan potensi wisata dan produk-produk unggulan yang dimiliki oleh desa (Anwar et al, 2020;Osin et al, 2020;Rokhani & Hafidhuddin, 2022). Dalam proses pembuatan website desa, perlu adanya pendampingan agar desa dapat memiliki sumber daya manusia yang mampu mengelola dan memperbaharui konten website secara mandiri (Riyanto & Kurniawati, 2018;Widiastini et al, 2018).…”
Section: Pendahuluanunclassified
“…Another study conducted by Rahmawati et al, (2022) in Gubugklakah Tourism Village, Poncokusumo District, Malang Regency found that the understanding of digital marketing in the village has increased as evidenced by efforts to increase content insights using paid advertising. Similarly, research from Rokhani and Hafidhuddin (2022) produces digital content so that the management of social media in Penglipuran Village, Bangli District, Bangli Regency can help in attracting visitors to come. However, in contrast to the findings from the research of Talalu et al, (2021) found several obstacles in digitalization such as limited internet network access, lack of promotional tools, to the unavailability of human resources who master digital marketing.…”
Section: Introductionmentioning
confidence: 99%